(untitled) (Communication & Society, 2001)
The present study tests the theory of selective exposure during 1996 national election campaign in Spain. Two main hypothesis are explored. The first one concerns the relationships between vote recall and media consumption, that is to say, the tendency of citizens to prefer media which are consonant with their ideology and political beliefs and to reject those which they perceive as dissonant with them. The second hypothesis objective is to prove that media in Spain have a highly politicized agenda analyzing the content of some national (El País and El Mundo) and two television channels (TVE1 and Antena 3).